2018
DOI: 10.2478/humo-2013-0026
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of lower limbs during V2 Al ternate in Nordic combined athletes

Abstract: Purpose. The aim of this study was to analyse the foot pressure distribution by cross-country skiers during the push-off phase when using the V2 Alternate skating technique depending on lower limb preference. The study also focused on whether push-off during V2 Alternate would be performed more quickly and in a shorter time interval by the dominant leg than the non-dominant leg. Methods. Data were collected using a pedographic system together with synchronised video recording. Conventional dialogistic methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Their study of laterality during symmetrical ski turns showed that the functional preference of the lower limb can affect the execution of a turn, even in the case of professional skiers. Furthermore, Jandová and charousek [21] performed an evaluation of ski runners and demonstrated that even for motions such as a two-step glide (V2 Alternate), which is symmetrical, the kick off will be performed quicker and in a shorter time by the dominant leg. The practical meaning of this is that when training, the ski runners should focus on improving their explosive power, especially in the case of the non-dominant leg.…”
Section: Discussionmentioning
confidence: 99%
“…Their study of laterality during symmetrical ski turns showed that the functional preference of the lower limb can affect the execution of a turn, even in the case of professional skiers. Furthermore, Jandová and charousek [21] performed an evaluation of ski runners and demonstrated that even for motions such as a two-step glide (V2 Alternate), which is symmetrical, the kick off will be performed quicker and in a shorter time by the dominant leg. The practical meaning of this is that when training, the ski runners should focus on improving their explosive power, especially in the case of the non-dominant leg.…”
Section: Discussionmentioning
confidence: 99%